2019
DOI: 10.3390/polym11101543
|View full text |Cite
|
Sign up to set email alerts
|

Urethane Formation with an Excess of Isocyanate or Alcohol: Experimental and Ab Initio Study

Abstract: A kinetic and mechanistic investigation of the alcoholysis of phenyl isocyanate using 1-propanol as the alcohol was undertaken. A molecular mechanism of urethane formation in both alcohol and isocyanate excess is explored using a combination of an accurate fourth generation Gaussian thermochemistry (G4MP2) with the Solvent Model Density (SMD) implicit solvent model. These mechanisms were analyzed from an energetic point of view. According to the newly proposed two-step mechanism for isocyanate excess, allophan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…All authors agreed that the addition of a hydroxy group to the C=N was more preferable and showed the importance of autocatalysis. Application of the hybrid SMD model by Cheikh et al [ 311 ] showed that isocyanates may also participate in the autocatalytic pathway for urethane formation.…”
Section: Case Studies For Connection Of Computational Chemistry and Kinetic Modelingmentioning
confidence: 99%
“…All authors agreed that the addition of a hydroxy group to the C=N was more preferable and showed the importance of autocatalysis. Application of the hybrid SMD model by Cheikh et al [ 311 ] showed that isocyanates may also participate in the autocatalytic pathway for urethane formation.…”
Section: Case Studies For Connection Of Computational Chemistry and Kinetic Modelingmentioning
confidence: 99%
“…So far, mechanistic studies on metal complex catalyzed PU reaction have been performed mainly for organotin catalysts, 58,[60][61][62][63][64][65] leaving critical questions still unanswered. It remains for example unclear what factors determine the selectivity and speed of the isocyanate-hydroxyl reaction when catalyzed by tin, zirconium, bismuth, or zinc catalysts.…”
Section: Mechanistic Investigation and Density Functional Theory Calcmentioning
confidence: 99%
“…Note that the effective rate of the urethan bond forming reaction can be influenced by various phenomena such as catalysis, autocatalysis, solvent effects and molecular interactions. 63,[66][67][68][69] Computations reveal that cyclic, tetrameric bismuth tricarboxylate clusters form thermodynamically driven by a free energy difference of −40 and −18 kJ mol −1 at 25°C and 60°C, respectively (Fig. 6).…”
Section: Mechanistic Investigation and Density Functional Theory Calcmentioning
confidence: 99%
“…Moreover, Raspoet et al also showed that auto-catalytic mechanisms are favorable compared to non-catalytic mechanisms in agreement with other studies discussed above. Recently, Cheikh et al [38] used more sophisticated quantum chemical methods to study autocatalytic urethane formation. The authors computed paths in energy, enthalpy and free energy based on the G4MP2 [53] protocol and the SMD solvation model.…”
Section: Introductionmentioning
confidence: 99%